Site fidelity of intertidal fish to rockpools - Roma, J. (2020)
Gobius paganellus, Lipophrys pholis and Coryphoblennius galerita are wide‐spread intertidal fish that spend their earlier life stages in rock pools, and yet very little is known about their site fidelity behaviour. For these species, fidelity to rockpools may result in increased fitness costs in a predicted scenario of warmer sea water, due to the low thermal inertia of these water bodies. In this context, it is relevant to investigate these species' site fidelity. We made a mark‐recapture study to assess the mentioned species' movements within and between rockpools. We tagged a total of 530 individuals of the aforementioned species with the Visible Implant Elastomer and tracked their movement for a 7‐month period. We found that site fidelity and specific rockpools conditions are important factors in distribution of intertidal blennies and gobies. We also examined the relations between rockpool volume, depth and site fidelity. We found that G. paganellus tends to remain in its original marking pool, with an average recapture rate of 20.5%, but showed no evidence of inter‐pool movement. Rockpool depth, however, proved to be important in the blennies' movements. Our findings are among the first to prove that a mark‐recapture method can be successfully used to track intertidal fish movements. In particular, we showed that G. paganellus presents site fidelity in intertidal rockpools during its early ontogeny for a period of two to three months.